Peripheral ameloblastoma: A case report - Ülker, Ersin (J Clin Exp Dent, 2020)
BACKGROUND: Ameloblastoma is a rare tumor which develops from odontogenic epithelium and its remnants and it occurs in the jaws. Peripheral ameloblastomas are rare and benign extraooseous ameloblastomas which effects soft tissues. This case report declares a peripheral ameloblastoma which is a rare type of ameloblastoma. MATERIAL AND METHODS: 34 year old female patient referred with a complaint of a gingival growth at right lower premolar area. A firm and granular surfaced gingival growth with the color of pink and red and having 1.5x1 cm sizes was observed at the mentioned area. With an incision from lower right second incisor tooth to lower right second molar tooth a flap from bone was made and lesion was excised. After then specimen was submitted to histopathologic examination. After clinical, radiological and pathological examinations lesion was described as peripheral ameloblastoma. RESULTS: At the control examination after three months of excision there was no recurrence and patieant has no complaint. CONCLUSIONS: Although reccurens rate of peripheral ameloblastomas are low, long-term follow-ups are suggested Patient was informed about the importance of regular controls for early diagnosis of possible reccurenses and regular controls were made during one year after excision. Key words:Peripheral ameloblastoma, gingiva, gingival hyperplasia, gingival lesion, alveolar mucosa, extraosseous.